Use of conventional bioanalytical devices to automate DBS extractions in liquid-handling dispensing tips. (October 2011) - Johnson, Casey JL; Christianson, Chad D; Sheaff, Chrystal N; Laine, Derek F; Zimmer, Jennifer SD; Needham, Shane R
Background: Conventional liquid-handling devices were employed, along with an improved punching device, to semi-automate dried blood spot (DBS) extraction of alprazolam, α-hydroxyalprazolam and midazolam from human whole blood. Liquid-handling devices were used to add internal standard to the DBS cards and to extract the analytes from the DBS, in order to be analyzed by HPLC–MS/MS.Results: The technique was shown to be accurate (±12.0%) and precise (10.3%) across the dynamic range of the assay.Conclusion: The semi-automated extraction reduced sample preparation time by more than 50% when compared with more conventional DBS manual extraction methods.